The Impact of Ferry Services on an Island Economy - Malcolm Greig; Ron McQuaid (European Regional Science Association (ERSA), 2005)
This paper examines ferry fares and quality of service to a remote island region and analyses how this affects the economy of the islands. Taking the Western Isles in Scotland as a case study, the paper identifies the links between fares, service, and economic development and attempts to quantify this impact. A new methodology is developed to estimate the impact of service frequency. The Western Isles, especially the more remote southern islands, face particular challenges due to their peripheral location relative to markets and supplies in Scotland, the rest of the UK and the European 'core'. This manifests itself in terms of access to skilled labour, raw materials, connections to other businesses and customers. These economies are likely to experience higher transportation costs to domestic and international markets and may also be limited by the frequency and reliability of connections. The ferry services between islands and with mainland Scotland are vital to the continued economic and social well-being of the Western Isles. The extent of the contribution of ferry services towards the economic and social prosperity of the Isles is very much dependant upon the frequency, speed and reliability of service and on the fare structure. It is therefore vital to ensure that the correct fare mechanism is in place to ensure maximum benefit to the local economy of the Isles, in addition to satisfying value for money criteria for the taxpayer and commercial viability for the operators. Our findings show that a reduction in ferry fares and, in particular in increase in service frequency, will have substantial income and employment benefits to the local economy, running into millions of pounds annually. It is also revealed that there is potential to increase the quality of service to the Isles, and reduce fares in some cases, with no increase in public subsidy towards operating costs. This is achieved by taking a more radical perspective to the routes and services operated, and by more closely matching service provision to the demands of communities within the islands.
Keywords: 330